Optical single sideband modulation with tunable optical carrier-to-sideband ratio using DP-BPSK modulator. (April 2021) - Wang, Chuangye; Ning, Tigang; Li, Jing; Pei, Li; Zheng, Jingjing; Xie, Caijian; Dong, Xiaowei
Highlights: We propose an approach to achieving single sideband modulation with tunable OCSR. The scheme can achieve tunable OCSR from −20 dB to 38 dB. The structure of the scheme is simple. This scheme can adjust OCSR by adjusting the angle of PC2. Abstract: In this paper, a novel approach to achieving optical single sideband modulation with tunable carrier-to-sideband ratio (OCSR) is proposed and demonstrated. The key of the scheme is a DP-BPSK (Dual Polarization BPSK) modulator. The DP-BPSK modulator is integrated and consists of two parallel dual-drive Mach-Zehnder modulator, an optical power splitter, a 90° polarization rotator, and a polarization beam combiner. The upper modulator of the DP-BPSK modulator is set to single sideband modulation and the lower modulator of DP-BPSK modulator is not modulated by radio frequency, then we can achieve a single sideband modulation signal with tunable OCSR by adjusting the angle of PC2. The scheme uses only one light source, one signal generator, one 90° hybrid coupler, one DP-BPSK modulator, two polarization controllers, one DC power supply and one linear polarizer. Compared with optical filter, optical grating, multiple modulators or other devices used in the previous schemes, the proposed structure is much simpler. The proposed approach is first theoretically analyzed and then verified by experiment. The single sideband modulation signals are obtained with a wide OCSR range of −20 dB to 38 dB in the experiment, and the performance of the scheme in the transmission link is also verified by simulation.